Analysis of Risk Factors For Nutritional Status and Consumption Patterns Among Pregnant Women With Chronic Energy Deficiency (CED) In The Working Area of A Public Health Center - Rya Anastasya Siregar (Jurnal Ners, 2026)
Chronic energy deficiency (CED) in pregnancy remains a persistent public health problem in Indonesia, contributing to adverse maternal and neonatal outcomes. Although quantitative surveys have mapped its prevalence, the socio-cultural and behavioral mechanisms that shape the nutritional status and diets of affected women remain poorly understood. This study aimed to explore CED risk factors and dietary patterns of pregnant women through a comprehensive qualitative study. A descriptive phenomenological study was conducted in a community health center (Puskesmas) in Bogor Regency, involving 25 participants: 15 pregnant women with an upper arm circumference <23.5 cm, five family members, and five health workers. Data were collected through in-depth interviews, focus group discussions, and observations, and then analyzed using Braun and Clarke's thematic analysis. Five key themes emerged: fragmented nutrition knowledge and misinformation; deeply ingrained food taboos and restrictive dietary practices; economic vulnerability and intra-household food allocation; fragmented family and partner support; and emotional distress related to food insecurity. The interplay of these factors creates a cycle of inadequate intake that cannot be broken by traditional nutrition education alone. These findings emphasize the need for culturally sensitive, family-centered interventions, integrating mental health support, economic empowerment, and reorientation of antenatal care to address the root causes of CED.